If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -8d = 39 Solving 7 + -8d = 39 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -8d = 39 + -7 Combine like terms: 7 + -7 = 0 0 + -8d = 39 + -7 -8d = 39 + -7 Combine like terms: 39 + -7 = 32 -8d = 32 Divide each side by '-8'. d = -4 Simplifying d = -4
| 1.08y=y+48 | | 3x-55+2x=5y | | Y+4.7=-8.6-5.3 | | -4x+6-5(x-1)=-(3x-3)-5x+5 | | X-0.2=6.4 | | 5x-2(3-4x)=3(x-3)-57 | | (4f^2-3)+11f=0 | | 5x+18+3x+34=90 | | y-7=-2.66(x-10) | | 42y+16= | | 4(2x+2)+5=3+2(4x+5) | | Z-2.8=10.9 | | Y/0.2=0.8 | | 16a^2+24ab+9b=(a+3b) | | (8x-8)/7=-8 | | y-7=0.66(x-10) | | 8=2v | | 2-(2x+3)=-11 | | 6x+5=5x+11 | | 0.5a=1.5 | | 3y-8+y+56=6y+50-4y | | (-3/4)²x | | 0.09xX=78.73 | | 12x+5=8x-17 | | 3m+5m=10 | | (-3/4)²*x | | 2x+7y=33.00 | | (-3/4)² | | -5+x=2y | | -43+5y+4=3(3y-3)-6 | | -48+4x=x | | 2-5-14=0 |